Penerapan Community Based Tourism sebagai Strategi dalam Pengelolaan Wisata - Amelia Wahyuningtiyas; Tukiman Tukiman (Universitas Musamus, Merauke, Papua, 2022)
Village communities should be given the opportunity to be involved or actively participate in the preparation of a tourism potential management project in the village. Taman Wisata Genilangit was established on land owned by Perhutani KPH Lawu Ds. In its management, local community participation is driven to manage existing tourism potential, so this is also a form of Community Based Tourism. Karang Taruna Genilangit Village as a community that initiates the participation or involvement of the village community. This study aims to determine the application of Community Based Tourism as a strategy in tourism management at Taman Wisata Genilangit. This study uses descriptive qualitative research methods, with data collection techniques in the form of interviews, observations and documentation. The result of this research is the achievement of the implementation of Community Based Tourism on the economic dimension, social dimension, cultural dimension, environmental dimension, and political dimension at Taman Wisata Genilangit. The indicators of a good waste management system at Taman Wisata Genilangit have not been fulfilled because they are still managed simply and there is no final disposal site, but the manager has been able to process the waste in Taman Wisata Genilangit. The tourism management in Taman Wisata Genilangit has a positive impact on the community by empowering local communities and maintaining active participation from the Genilangit Village community.